INTENSITAS DAN TIPE SERANGAN PENGGEREK KAYU DI PERAIRAN PULAU RAMBUT DAN PUNTUNG JAWA - Mohammad Muslich; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan, 1988)
One  hundred   fifty   pieces  of  wood  consisting  of  15 species  were randomly   arranged in form  of  a raft and  floated at Rambut and Puntung  Java Islands seashore. The size of the wood  specimens  is 2,5 cm x 5 cm x 30 cm.                      The  samples  were  tested  against  two  principal  family of  marine  borers,   i.e.   teredinids  and pholads  and  evaluated after three  months. The  results  reveal that  most  of  the  tested  woods  were severely  attacked  by  teredinids,  except   Heritiera  littoralis, Heritiera javanica, Diospyros celebica, and  Eucalyptus platyphylla, but  these  species  were severely  attacked by pholads.  The infestation has two distinct  types,  characterited by its structure  and pattern  of  wood  boring